2010
DOI: 10.1007/s00270-010-9796-z
|View full text |Cite
|
Sign up to set email alerts
|

A Case of Lipiduria After Arterial Embolization for Renal Angiomyolipomas

Abstract: We report the case of a 31-year-old woman who suffered lipiduria after selective transcatheter arterial embolization for renal angiomyolipoma (AML). Computed tomography confirmed cystic liquefactive necrosis with fat-fluid level in AML. Although the process by which AML fat tissue excretion occurs is not clear, we speculated that the infarcted AML was connected to the urinary collection duct system and subsequently its adipose component was excreted into the urine.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
16
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(16 citation statements)
references
References 8 publications
0
16
0
Order By: Relevance
“…To the best of our knowledge, such renal colic due to fatty tissue migration into the collecting system has never before been reported. Nonetheless, Ishibashi et al 8 already reported a case of asymptomatic lipiduria following arterial embolisation of an AML.…”
Section: Discussionmentioning
confidence: 99%
“…To the best of our knowledge, such renal colic due to fatty tissue migration into the collecting system has never before been reported. Nonetheless, Ishibashi et al 8 already reported a case of asymptomatic lipiduria following arterial embolisation of an AML.…”
Section: Discussionmentioning
confidence: 99%
“…One vial of 300-500-micron Embosphere® (BioSphere Medical) was used for the embolization of feeding vessels. There is a correlation between RAML size and the appearance of symptoms and complications [1][2][3][4][5][6][7][8][9]14,16 . The most frequent sign, in 85% of the cases, is abdominal or lumbar pain 1,6,7,10,13,16 .…”
Section: Discussionmentioning
confidence: 99%
“…Angiomyolipomas (AML) are rare benign tumors that account for 2% to 3% of all renal tumors [1][2][3][4][5][6][7] . They are twice more frequent among women 1,5,6,8 . Most are sporadic, but 10% are associated with tuberous sclerosis complex (TSC) [1][2][3][4][5][6][7][9][10][11] .…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations